The God of whom? : From a psychological to a systematic-theological intertwining of black liberation theology and anatheism - Veldsman, Daniel Petrus (University of Pretoria, 2024)
Dissertation (MTh (Dogmatics and Christian Ethics))--University of Pretoria, 2023.